From the Other Half to the Down and Out: Reflections on Poverty in the Documentary Mode - Jasmin Humburg (Current Objectives of Postgraduate American Studies)
This article investigates how poverty is negotiated in the social documentary mode. By considering the work of Jacob Riis and Lewis Hine as well as scrutinizing two HBO documentaries, Down and Out in America“ (1985) and American Winter“ (2013), I argue that there is a continuous disparity between those who represent and those who are being represented. I will exemplify how this imbalance is facilitated through visual rhetoric and narrative form in documentary representations of poverty.